The Influence of Knowledge Sharing and Competency on Teacher Performance Through Individual Innovation Capability at SMAN 2 Bangkalan - Faqih, Alief Abdullah; Sukarno, Gendut (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to examine the influence of knowledge sharing and competence on teacher performance at SMA Negeri 2 Bangkalan through individual innovation capability. In this context, knowledge sharing and competence are considered crucial for creating good performance in schools. This research employs a quantitative method with the help of a questionnaire to collect data from a sample of 73 respondents. Data analysis is conducted using the Partial Least Squares (PLS) method. The results show that knowledge sharing has a positive and significant effect on teacher performance, as does competence. Furthermore, knowledge sharing and competence also have a positive and significant effect on teacher performance through individual innovation capability. These results indicate a mutually influential relationship between knowledge sharing, competence, individual innovation capability, and teacher performance at SMA Negeri 2 Bangkalan.